Psychology in society (PINS) and traditions: Back towards a critical African psychology - Ratele, Kopano (PINS-Psychology in Society, 2025)
Tradition is an ubiquitous yet in the main veiled question in the annals of Psychology in Society (PINS) and critical psychology. The traditions I have in mind are what might be provisionally be referred to as “African traditions”. Critical psychology seems to be comfortable with neglecting doing some self-examination on its African traditions or absence thereof. In this article I thus reflect on PINS’s and critical psychology’s knowledge traditions, including our intellectual ancestry, and their dis/connections to Africa. I suggest that we might want to ask ourselves questions such as what, for whom is, and why a critical psychology, in a recently liberated society, on this continent, today, if it is not simply and mainly opposed to mainstream psychology. I contend that it is important within the context of imperial and colonial knowledge that marginalises thought from the global South for critical psychologists to account for their own traditions, not only others’ traditions, and link to critical African thought from beyond our borders.